Unexpected formation of a co-crystal containing the chalcone (E)-1-(5-chlorothiophen-2-yl)-3-(3-methylthiophen-2-yl)prop-2-en-1-one and the keto–enol tautomer (Z)-1-(5-chlorothiophen-2-yl)-3-(3-methylthiophen-2-yl)prop-1-en-1-ol - Mahmoud Al-Refai; Basem F. Ali; Armin Geyer; Klaus Harms; Michael Marsch (Acta Crystallographica Section E: Crystallographic Communications, 2020)
The title crystal structure is assembled from the superposition of two molecular structures, (E)-1-(5-chlorothiophen-2-yl)-3-(3-methylthiophen-2-yl)prop-2-en-1-one, C12H9ClOS2 (93%), and (Z)-1-(5-chlorothiophen-2-yl)-3-(3-methylthiophen-2-yl)prop-1-en-1-ol, C12H11ClOS2 (7%), 0.93C12H9ClOS2·0.07C12H11ClOS2. Both were obtained from the reaction of 3-methylthiophene-2-carbaldehyde and 1-(5-chlorothiophen-2-yl)ethanone. In the extended structure of the major chalcone component, molecules are linked by a combination of C—H...O/S, Cl...Cl, Cl...π and π–π interactions, leading to a compact three-dimensional supramolecular assembly.